Evaluation Of The Disaster Resilient Village (Destana) Program In Wedoro Village, Waru Subdistrict, Sidoarjo Regency - Septyaningrum, Dita Puspita; Wibawani, Sri (UNIVERSITAS PAKUAN, 2024)
Indonesia's geographical location makes it a country prone to natural disasters. The effects of climate change in Indonesia also cause environmental damage that results in disasters. The cause of a series of natural disaster symptoms cannot be separated from human actions that damage nature, so disaster mitigation needs to be done as a form of anticipation. Disaster management in each region has a particular institution, the National Disaster Management Agency, abbreviated as BNPB. One of the BNPB programs that aims to increase the independence and resilience of communities living in vulnerable areas is the Destana program. Wedoro in Waru Subdistrict is a disaster-prone area, especially in floods, and has been running the Destana program since 2022. Researchers are interested in researching the evaluation of the Destana program in Wedoro. The purpose of the research is to evaluate and provide recommendations for the Destana program in Wedoro according to 6 indicators in the form of effectivity, efficiency, adequacy, equity, responsivity, and accuracy. The type of research conducted is descriptive qualitative, using the William N. Dunn evaluation method and data collection techniques of observation, interview, and documentation. The results showed that of the six fulfillment of evaluation indicators, there was one indicator that had not gone well, namely the efficiency indicator, due to the lack of utilization of human resources, so it could be concluded that the Destana program in Wedoro could be continued by increasing human resources in Wedoro Village.